Institutionalised Sufism and Epistemic Integration: The Naqshbandi al-Khalidiyya Da’imiyya Order in Contemporary Indonesia - Muklis Siregar; Elly Warnisyah Harahap; Syahrin Harahap (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2025)
This study analyzes how the Tarekat Naqsyabandiyah Al-Khalidiyah Da’imiyah (TNKD) constructs and institutionalizes the integration of spiritual discipline and scientific rationality within contemporary Sufi practice. In the context of modernity, religious traditions are often perceived as incompatible with rational, scientific modes of knowledge, thereby marginalizing Sufi institutions. However, emerging forms of organized Sufism indicate a more complex negotiation between spirituality, rationality, and institutional life. This research employs a qualitative design using a spiritual ethnography approach, involving participant observation and in-depth interviews with key TNKD authorities. Data were analyzed through condensation, display, and verification within an interpretive epistemological framework. The findings reveal, first, that TNKD has transformed into an institutionalized and expansive Sufi order in which formal organizational structures enable sustainability and transregional growth without eroding spiritual authenticity. Second, TNKD’s spiritual legitimacy is grounded in a muktabarah silsilah and a stratified authority structure that ensures doctrinal continuity and communal trust. Third, TNKD integrates the Sufi discipline with scientific rationality through intellectual forums, academic writing, and evaluative mechanisms, thereby positioning tasawuf as a reflective and accountable knowledge tradition. This study contributes theoretically by conceptualizing Sufism as an epistemic institution and recommends further comparative research on rationality within contemporary Sufi orders.